GPS vehicle tracking system - android application - Nurhikmah Binti Robani (School of Microelectronics, University Malaysia Perlis, 2015)
Nowadays, the cases of vehicle theft are often to be heard. The loss vehicle may be used by criminals to commit crimes such as kidnapping, smuggling and robberies. Installing a GPS tracking device in the vehicle can help to monitor its location. This tracking device can be really useful for company that provide courier service and car rental company. I will also describe an android application that shows locations of the vehicle in google maps. Username and password field are the safety feature provided by this application. After these fields have been filled, user can search for the coordinates of the vehicle. Once the coordinates has been detected, the application shows location on google maps in real-time.